You have the following system of equations:
y =6x - 11
-2x - 3y = -7
in order to solve the previous system by using the substitution method, proceed as follow:
replace the expression y=6x-11 into the second equation, and solve for x:
-2x - 3(6x - 11) = -7
-2x - 18x + 33 = -7
-20x + 33 = -7
-20x = -7 - 33
-20x = -40
x = -40/(-20)
x = 2
next, replace x=2 into the first equation to obtain the value of y:
y = 6(2) - 11
y = 12 - 11
y = 1
Hence, the solution to the given system of equations is
x=2
y=1